Pengembangan Buku Teks Matematika Kelas 8 Dengan Model ADDIE - Andhi Soesilo; Ashiong Parhehean Munthe (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Textbook is one of the primary resources to support teaching and learning. From the survey of the target school, the current secondary mathematics textbook does not match with Curriculum 2013 and heavy in size. Based on that survey, need analysis was conducted and it was recommended that the requirement of the textbook aligned with 2013 Curriculum, using proper English, and light in size. This research purpose is to produce the secondary mathematics textbook that matches the school’s need. The method of research is Research and Development with model of ADDIE. The study was conducted in a private school in Jakarta with 96 students of grade 8 and 10 teachers in 2018. Instruments used are need analysis, validity expert, and test. Analysis of data use description of expert judgment based on content, language and design criteria and descriptive statistic for pre-test and post-test. The result was the textbook is valid and matches with the needs of that school.